AGRICULTURE AS A UNIFER OF SECURITY AND DEVELOPMENT IN THE FACE OF FREE MARKET CHALLENGES - Krzysztof PRENDECKI (Humanities and Social Sciences)
Individual stages of the implementation of sustainable development should be important to people in their drive toward effective production and economic goals. Successful implementation is vital to maintaining access to food. Sustainable development should ensure sufficient food supply for the population in various living conditions, maintain compliance with food health safety, and keep the needs of biodiversity into consideration. Over the last few decades, agriculture has undergone a huge change, and attention should be paid to the quality of food products, the fulfillment of conditions, and actions that must be taken at many stages of production and food trade in order to ensure an adequate human existence. A look at agriculture also allows us to see its multifunctionality in a changing global world. Ensuring food security, without violating ecological security, while maintaining elements of rural culture, presents significant challenges for national and global agrarianism. The neoliberal approach should also take into account not only the financial dimension but also the broader perspective of social responsibility.